PENDEKATAN PSIKOLOGI DALAM KAJIAN PENDIDIKAN ISLAM - Firman Mansir (Psikis : Jurnal Psikologi Islami, 2018)
This study examines psychology as an approach in Islamic studies, especially in Islamic education. Islamic psychology and education basically have the same pattern in seeing various cases in scientific buildings, so that in Islamic studies such as Islamic education, an approach is required to look at deeper social phenomena, namely by using a psychological approach. This research is literature study (library research) that is research which come from library materials by using qualitative approach. Therefore, what is done is the exploration of some data both primary and secondary data with concrete steps as follows: read and examine in depth primary data such as books which is the result of research, thesis or dissertation related to psychology and education of Islam. Therefore, psychology as an approach can give birth to findings that fit the context. In Islamic studies, especially Islamic education can be access for other sciences to serve as a tool in viewing various social problems. It then happens with the psychology and education of Islam because it gave birth to the psychology of Islamic education.